Can we fly less? Evaluating the 'necessity' of air travel. (October 2019) - Gössling, Stefan; Hanna, Paul; Higham, James; Cohen, Scott; Hopkins, Debbie
Abstract: Air travel is often justified as 'necessary' or 'unavoidable', in the sense that trips have purpose and value. Yet it is evident that people travel for reasons that may include forced and voluntary movement, with motives ranging from visiting friends and family, to leisure, or business. In light of the challenge to decarbonise transport, and the need to reduce greenhouse gas emissions, this paper discusses the perceived necessity of flight from individual and societal perspectives, while considering moral and economic viewpoints. It suggests that travel motives have different degrees of 'urgency', and that the 'necessity of flight' cannot be generalised. To empirically test this hypothesis in an exploratory survey, we used mixed methods to examine the perspectives of 29 international students at Lund University, Sweden on the perceived importance of their flights (n = 587) over a six-year period (2012–2017). Results show that the value associated with individual flights depends on flight motive, experience, life stage, or situational factors. Notably, almost half of the leisure flights made lack importance. Implications are discussed in the context of climate policy and the future development of the aviation system. Highlights: Discusses economic and moral perspectives on the necessity of air travel. Suggests that perspectives on flight vary between motives, individuals and socities Indicates that large share of air travel may be considered redundant by travelers. Highlights differences in the importance assigned to flight.